2019
DOI: 10.3390/coatings9120842
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Simulation of Multi-Slip Effects on Unsteady MHD Bioconvective Micropolar Nanofluid Flow Over a Sheet with Solutal and Thermal Convective Boundary Conditions

Abstract: In this article, the intention is to explore the flow of a magneto-hydrodynamic (MHD) bioconvective micro-polar Nanofluid restraining microorganism. The numerical solution of 2-D laminar bioconvective boundary layer flow of micro-polar nanofluids are presented. The phenomena of multi-slip, convective thermal and Solutal boundary conditions have been integrated. A system of non-linear partial differential equations are transformed into the system of coupled nonlinear ordinary differential equations by applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 108 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…Additionally, it is very proficient and has been applied to study the miscellaneous problems in fluid mechanics, and in computational fluid dynamics, solid mechanics, mass transfer, heat transfer, and many other fields [33]. Reddy [34] demonstrates an admirable universal feature of the variational finite element method, and confinement in various nonlinear problems, such as simulating the transmission phenomenon of unsteady magnetohydrodynamic [26,35,36] and mixed convection micropolar flow in porous media [37]. In order to apply the finite element method (FEM) to the simultaneous nonlinear differential Equations (9)-(12), and to use the boundary conditions in the Equations (13) and (14), we consider:…”
Section: Finite Element Methods (Fem) Solutionsmentioning
confidence: 99%
“…Additionally, it is very proficient and has been applied to study the miscellaneous problems in fluid mechanics, and in computational fluid dynamics, solid mechanics, mass transfer, heat transfer, and many other fields [33]. Reddy [34] demonstrates an admirable universal feature of the variational finite element method, and confinement in various nonlinear problems, such as simulating the transmission phenomenon of unsteady magnetohydrodynamic [26,35,36] and mixed convection micropolar flow in porous media [37]. In order to apply the finite element method (FEM) to the simultaneous nonlinear differential Equations (9)-(12), and to use the boundary conditions in the Equations (13) and (14), we consider:…”
Section: Finite Element Methods (Fem) Solutionsmentioning
confidence: 99%
“…This approach is better suited and more accurate than other numerical methods such as ADM, HPM, and FDM. It is also very proficient and has been applied in many other fields [34] to research various problems in fluid mechanics and computational fluid dynamics, solid mechanics, mass transfer, and heat transfer [24,35,36]. To apply FEM to the simultaneous nonlinear differential equations (Equations (11)-(14)), and to use the boundary conditions in Equations (15) and (16), we consider:…”
Section: Finite Element Methods Solutionsmentioning
confidence: 99%
“…Tian et al [23] examined the nanofluid rheological behavior of nanoparticles CuO/MWCNTs incorporated with base fluid water/EG (70:30) at the temperature 20-60 • C. Alsarraf et al [24] investigated the impact of the nanoparticle shape on the fluid flow features of boehmite alumina nanofluid in a horizontal double-pipe minichannel heat exchanger. Liaqat et al [25] explored the influence of multiple slips and the solutal boundary condition on magnetohydrodynamic unsteady bioconvective micropolar nanofluid-restrictive gyrotactic microbes, mass, and heat transference impact through the sheet. Ibrahim and Shankar [26] revealed that the heat transfer and the magnetohydrodynamic boundary layer flow of nanofluids via infiltration was able to stretch the sheet in velocity, thermal, and solutal-slip boundary conditions.…”
Section: Introductionmentioning
confidence: 99%